2004
DOI: 10.1021/ja038691x
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Raman Spectroscopy Reveals New Insight into the Electronic Structure of β-Hematin and Malaria Pigment

Abstract: Resonance Raman spectra of beta-hematin and hemin are reported for a range of excitation wavelengths including 406, 488, 514, 568, 633, 780, 830, and 1064 nm. Dramatic enhancement of A(1g) modes (1570, 1371, 795, 677, and 344 cm(-1)), ring breathing modes (850-650 cm(-1)), and out-of-plane modes including iron-ligand modes (400-200 cm(-1)) were observed when irradiating with 780- and 830-nm laser excitation wavelengths for beta-hematin and to a lesser extent hemin. Absorbance spectra recorded during the transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
165
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(186 citation statements)
references
References 49 publications
12
165
0
Order By: Relevance
“…95 The following year, they reported a more detailed Raman spectroscopic study of hematin (the synthetic analog of hemozoin). 96 In 2007 the Monash workers co-authored a study in which acoustic levitation was used to suspend RBCs and Plasmodium-infected cells in place, allowing the measurement of the spectral signature of hemozoin in the diseased cells. 97 One of the co-authors of that study, J. Popp, had previously been one of the early workers on LTRS.…”
mentioning
confidence: 99%
“…95 The following year, they reported a more detailed Raman spectroscopic study of hematin (the synthetic analog of hemozoin). 96 In 2007 the Monash workers co-authored a study in which acoustic levitation was used to suspend RBCs and Plasmodium-infected cells in place, allowing the measurement of the spectral signature of hemozoin in the diseased cells. 97 One of the co-authors of that study, J. Popp, had previously been one of the early workers on LTRS.…”
mentioning
confidence: 99%
“…Furthermore, the excitation in the 400-600 nm visible range induces resonant Raman scattering, which depends strongly on the laser wavelength [43]. This phenomenom is produced by electronic transitions associated to the Soret band [44] and the porphyrin ring (Q V and Q 0 bands) [40]. In our work, 488 nm laser excitation enhanced the Soret band scattering and totally symmetric vibrational modes n 2 , n 3 , and n 4 .…”
Section: Rbcs Raman Analyses Raman Spectra Of Rbcs Arise Mainly From mentioning
confidence: 69%
“…In contrast, the HRgpA-and Kgp-haem incubations resulted in a broadening of the Soret band and greater reductions in intensity, indicative of a greater extent of m-oxo dimer formation and aggregation compared to the control or the RgpB protease. Reduction of Soret band absorbance intensity and broadening are measures of the extent of dimerization (Inada & Shibata, 1962) and molecular aggregation of ferrihaems (Wood et al, 2004), respectively. On this basis it was clearly demonstrated that both HRgpA and Kgp mediated greater dimer formation and aggregation than RgpB, which lacks the HA2 domain.…”
Section: Resultsmentioning
confidence: 99%